Early life stress, prenatal secondhand smoke exposure, and the development of internalizing symptoms across childhood - Mariah DeSerisy; Jacob W. Cohen; Jordan D. Dworkin; Jeanette A. Stingone; Bruce Ramphal; Julie B. Herbstman; David Pagliaccio; Amy E. Margolis (BMC, 2023)
Abstract Background Prior findings relating secondhand tobacco smoke (SHS) exposure and internalizing problems, characterized by heightened anxiety and depression symptoms, have been equivocal; effects of SHS on neurodevelopment may depend on the presence of other neurotoxicants. Early life stress (ELS) is a known risk factor for internalizing symptoms and is also often concurrent with SHS exposure. To date the interactive effects of ELS and SHS on children's internalizing symptoms are unknown. We hypothesize that children with higher exposure to both prenatal SHS and ELS will have the most internalizing symptoms during the preschool period and the slowest reductions in symptoms over time. Methods The present study leveraged a prospective, longitudinal birth cohort of 564 Black and Latinx mothers and their children, recruited between 1998 and 2006. Cotinine extracted from cord and maternal blood at birth served as a biomarker of prenatal SHS exposure. Parent-reported Child Behavior Checklist (CBCL) scores were examined at four timepoints between preschool and eleven years-old. ELS exposure was measured as a composite of six domains of maternal stress reported at child age five. Latent growth models examined associations between SHS, ELS, and their interaction term with trajectories of children's internalizing symptoms. In follow-up analyses, weighted quintile sum regression examined contributions of components of the ELS mixture to children's internalizing symptoms at each time point. Results ELS interacted with SHS exposure such that higher levels of ELS and SHS exposure were associated with more internalizing symptoms during the preschool period (β = 0.14, p = 0.03). The interaction between ELS and SHS was also associated with a less negative rate of change in internalizing symptoms over time (β=-0.02, p = 0.01). Weighted quintile sum regression revealed significant contributions of maternal demoralization and other components of the stress mixture to children's internalizing problems at each age point (e.g., age 11 WQS β = 0.26, p < 0.01). Conclusions Our results suggest that prior inconsistencies in studies of SHS on behavior may derive from unmeasured factors that also influence behavior and co-occur with exposure, specifically maternal stress during children's early life. Findings point to modifiable targets for personalized prevention.